Progranulin and insulin-like Growth Factor Binding Protein-2 as Biomarkers of Disease Activity and Pathological Changes in Lupus Nephritis - Goma, Samar H.; Abdelaziz, Marwa Mahmoud; El-Hakeim, Eman H.; El Zohri, Mona H.; Sayed, Sohair K. (Aktuelle Rheumatologie, 2019)
Background Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease, characterised by the production of auto-antibodies and the formation of immune complexes due to the polyclonal activation of T and B lymphocytes, which results in tissue and organ damage. During inflammation, neutrophils and macrophages release serine proteases to cleave progranulin (PGRN) into granulin, which exerts its pro-inflammatory effects that counteract the anti-inflammatory effects of intact PGRN. It is suggested that insulin-like growth factor binding protein-2 (IGFBP-2) is a dependable biomarker of renal deterioration but it is still unclear if it has high sensitivity and specificity for discriminating SLE-caused kidney disease from other-cause kidney disease.This study aimed to investigate the diagnostic value of PGRN and ILGFBP-2 in patients with lupus nephritis (LN) and the correlation of these biomarkers with disease activity and renal biopsy pathology.Patients and methods Patients with SLE (n=25) and chronic kidney disease (CKD) (n=25), and age- and sex-matched controls (n=25) were enrolled in the study. Serum PGRN and ILGFBP-2 levels were measured for each group.Results Disease duration was 4.78±4.26 years in the SLE patients. The mean SLE Disease Activity Index score was 15.04±7.54. All renal biopsy results were class 2, 3, and 5 with a percentage of 32, 24, and 44% respectively. PGRN and ILGFBP-2 were significantly higher in SLE patients (p<0.001 all) than in the CKD and control groups. All patients with high levels of biomarkers showed higher values of SLE disease activity. No significant difference was noted between active and inactive LN or classes of renal biopsy with PGRN and ILGFBP-2.Conclusion PGRN and ILGFBP-2 are significantly elevated in SLE compared to CKD and the general population and were associated with the SLE Disease Activity Index but not with active LN or classes of renal biopsy.
Keywords: progranulin (PGRN); insulin-like growth factor binding protein (IGFBP-2); lupus nephritis; pathology